Scrummy Cookies / Nur Sufiah Mohd Supian and Nur Syakirin Abdul Rahim - Mohd Supian, Nur Sufiah; Abdul Rahim, Nur Syakirin (2022)
Scrummy Cookies is our own brand, which recently launched in November 2021. Scrummy Cookies are fresh, homemade baked cookies that come in two varieties: chocolate chip cookies and chocolate dip cookies. Our cookies are made with high-quality ingredient to maintain a scrumptious taste and a crispy texture that will satisfy our customers. Everyone can enjoy it because the price is affordable. As a result, target audience includes children, teenagers, students, young adults and working adults.